Toward scoping reviews of individual bird species. (24th February 2022) - McClure, Christopher J. W.; Szymczycha, Zackery; Anderson, David L.; Aguiar‐Silva, Francisca Helena; Schulwitz, Sarah; Dunn, Leah; Henderson, Michael T.; Camacho, Leticia; Vargas González, José de Jesús; Parish, Chris N.; Buechley, Evan R.; D'Elia, Jesse; et al.
Abstract : Scoping reviews, in which the literature on a given topic is systematically collated and summarized, aid literature searches and highlight knowledge gaps on a given topic, thus hastening scientific progress and informing conservation efforts. Because much research and conservation is targeted at the species level, ornithology and bird conservation would benefit from scoping reviews of individual species. We present and apply a framework for scoping reviews for three disparate raptor species: California Condor Gymnogyps californianus, Harpy Eagle Harpia harpyja and Gyrfalcon Falco rusticolus . We consulted expert panels to develop appropriate search strings and lists of essential literature, i.e. 'benchmark articles'. We searched Web of Science, Scopus and Google Scholar. Searches for California Condor, Harpy Eagle and Gyrfalcon returned 268, 138 and 343 articles, respectively, that discuss, review or collect empirical data for the focal species. Our searches returned all benchmark articles identified by species experts, indicating that the searches captured the most important work on each species. We coded each study according to the topic addressed, country and month in which data were collected. We also coded threats, stresses and conservation actions addressed by studies, following definitions used by the International Union for the Conservation of Nature (IUCN) during Red List assessments. Literature summaries for each species include the number of studies addressing certain topics, monthly timing of research and global maps of research focus. Our coding scheme revealed important knowledge gaps for each species. Effects of conservation actions on wild individuals were less studied for California Condors. Harpy Eagles were less studied outside of Brazil and Panama, and Gyrfalcons were less studied outside of their breeding season. Scoping reviews of the world's bird species would help to identify critical knowledge gaps, thereby aiding the global effort to assuage the sixth mass extinction.